Associations of clinical characteristics and treatment regimens with the duration of viral RNA shedding in patients with COVID-19. (September 2020) - Chen, Xudan; Zhu, Baoyi; Hong, Wenxin; Zeng, Jianwen; He, Xi; Chen, Jingfeng; Zheng, Haipeng; Qiu, Shuang; Deng, Ying; Chan, Juliana C.N.; Wang, Jian; Zhang, Yuying
Highlights: The median duration of viral RNA shedding was 12 days, with a few cases showing shedding for up to 5–6 weeks. Delayed hospital admission resulted in prolonged viral RNA shedding. Old age and diarrhea as a symptom were associated with prolonged viral RNA shedding. Corticosteroid should be used with caution due to the risk of delayed viral RNA clearance. Lopinavir/ritonavir tended to delay viral RNA clearance in patients with non-severe illness. Abstract: Objective: The novel coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a global pandemic, but the factors influencing viral RNA shedding, which would help inform optimal control strategies, remain unclear. Methods: The clinical course and viral RNA shedding pattern of 267 consecutive symptomatic COVID-19 patients admitted to the hospital from January 20, 2020 to March 15, 2020 were evaluated retrospectively. Results: The median duration of viral RNA shedding was 12 days (interquartile range 8–16 days) after the onset of illness. Of the 267 patients included in this study, 65.2% had viral RNA clearance within 14 days, 88.8% within 21 days, and 94.4% within 28 days. Older age (hazard ratio (HR) 0.99, 95% confidence interval (CI) 0.98–1.00; p = 0.04), time lag from illness onset to hospital admission (HR 0.91, 95% CI 0.88–0.94; p < 0.001), diarrhea (HR 0.59, 95% CI 0.36–0.96; p = 0.036), corticosteroid treatment (HR 0.60, 95% CI 0.39–0.94; p = 0.024), and lopinavir/ritonavir use (HR 0.70, 95% CI 0.52–0.94; p = 0.014) were significantly and independently associated with prolonged viral RNA shedding. Conclusions: Early detection and timely hospital admission may be warranted for symptomatic COVID-19 patients, especially for older patients and patients with diarrhea. Corticosteroid treatment is associated with prolonged viral RNA shedding and should be used with caution. Lopinavir/ritonavir use may be associated with prolonged viral RNA shedding in non-severe patients; further randomized controlled trials are needed to confirm this finding.